P-Glikoprotein sebagai Transporter Effluks yang Dapat Mempengaruhi Absorpsi Obat Oral - Millati Hanifa Suparno; Fitrianti Darusman; Hanifa Rahma (UNISBA Press, 2024)
Abstract. Oral drug administration is the most frequent route of administration for drug delivery systems. Oral drug administration designates members of the ATP binding cassette (ABC) transporter superfamily. In competitive inhibitors, when a substrate attempts to bind to the P-gp protein transport site for translocation, the competitive inhibitor competes with the drug substrate to occupy all accessible protein transport sites, so that P-gp cannot bind to the drug substrate...whereas in non-competitive inhibitors, the inhibitor binds to all osteris modulation sites and non-competitively inhibits protein efflux...Because of this non-competitive inhibitors are also known as non-transport inhibitors. Drug or substrate can enter the cell membrane through filtration, simple diffusion, or specialized transport..Drug efflux begins with drug identification by P-gp followed by ATP binding and hydrolysis..The energy generated from ATP hydrolysis is used to remove the substrate from the cell membrane through the central aperture.There are three models of P-gp-mediated drug efflux, namely the classical pore pump model, hydrophobic vacuum cleaner (HVC) model, and flippase model. Abstrak. Administrasi obat secara oral adalah rute pemberian yang paling sering untuk sistem penghantaran obat. Pemberian obat oral menunjuk anggota dari superfamily ATP binding cassette (ABC) transporter. 80% obat yang menghasilkan efek sistema oral.Pada inhibitor kompetitif, ketika substrat mencoba berikatan dengan situs transpor protein P-gp untuk translokasi, inhibitor kompetitif bersaing dengan substrat obat untuk menempati semua situs transpor protein yang dapat diakses, sehingga P-gp tidak dapat berikatan dengan substrat obat..Sedangkan pada inhibitor non-kompetitif, inhibitor berikatan dengan semua situs modulasi osteris dan secara non-kompetitif menghambat efluks protein..Karena itu inhibitor non-kompetitif juga dikenal sebagai inhibitor non-transport .Obat atau substrat dapat memasuki membran sel melalui filtrasi, difusi sederhana, atau transpor khusus..Efluks obat diawali dengan identifikasi obat oleh P-gp yang dilanjutkan dengan pengikatan dan hidrolisis ATP..Energi yang dihasilkan dari hidrolisis ATP digunakan untuk mengeluarkan substrat dari membran sel melalui lubang pusat (central aperture).Terdapat tiga model efluks obat yang dimediasi P-gp, yaitu classical pore pump model, hydrophobic vacuum cleaner (HVC) model, dan flippase model.